The Science of Fat Grafting - Shih, Linden; Davis, Matthew J.; Winocour, Sebastian J. (Seminars in Plastic Surgery, 2020)
Autologous fat grafting has become a popular and well-established technique used by plastic surgeons in a variety of aesthetic and reconstructive procedures. An understanding of the basic science principles underlying fat grafting is crucial to explaining its extensive utility for soft tissue rejuvenation, volume augmentation, and body contouring—and the unpredictable fat resorption rates after grafting that pose a significant challenge for plastic surgeons. While the scientific principles of fat grafting can theoretically be exploited to optimize fat grafting techniques and increase fat tissue survival, a consensus has yet been established as to the best practices for this procedure. This review discusses the biology of adipose tissue and the scientific principles behind its behavior and survival in autologous fat grafting.
Keywords: autologous fat grafting; adipocyte regeneration; adipogenesis; adipose-derived stem cells; fat graft survival